Preparation method and application of carbon fiber paper for gas diffusion layer of electrolytic cell

CN122980265APending Publication Date: 2026-10-27SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610793447.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

目前,在氢能源领域,大多数碳纸的研究集中在燃料电池用气体扩散层的应用,关于质子交换膜电解槽阴极气体扩散层用碳纸研究较少

Benefits of technology

[0037](1)提供了一种电解槽气体扩散层用碳纤维纸的制备方法,其中碳纤维经过磺酸化改性后,表面引入磺酸基团(-SO3H),增强了其亲水性和分散能力。同时,适当地使用分散剂可以协助碳纤维更加均匀稳定地分散在水溶液中。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122980265A_ABST
    Figure CN122980265A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of carbon fiber paper for an electrolytic cell gas diffusion layer. After sulfonic acid modification of carbon fibers, sulfonic acid groups (-SO3H) are introduced on the surface of the carbon fibers, thereby enhancing hydrophilicity and dispersion capacity of the carbon fibers. Meanwhile, proper use of a dispersant can help the carbon fibers to be more uniformly and stably dispersed in an aqueous solution. A multi-walled carbon nanotube is subjected to amino modification by using an amine compound, so that the surface of the multi-walled carbon nanotube has amino groups (-NH2), thereby generating electrostatic force with the -SO3H groups of the modified carbon fibers, and the binding force between the carbon fibers and the multi-walled carbon nanotube can be effectively enhanced. In addition, polyacrylonitrile pulp with a large specific surface area can improve the retention rate of the multi-walled carbon nanotube, thereby improving the electric conductivity, bending strength and tensile strength of the carbon fiber paper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of high-performance fiber paper-based materials, specifically relating to a method for preparing carbon fiber paper for the gas diffusion layer of an electrolytic cell and its application. Background Technology

[0002] Carbon fiber paper is a high-performance two-dimensional material made from carbon fibers, possessing excellent electrical and thermal conductivity, high-temperature resistance, and chemical stability. In the field of green water electrolysis for hydrogen production, carbon fiber paper is a core material of the gas diffusion layer in proton exchange membrane electrolyzers, directly affecting the efficiency of proton exchange membrane water electrolysis. It must meet stringent requirements such as porosity, low electrical resistance, and chemical stability. Furthermore, it is widely used in fuel cells, electromagnetic shielding, antistatic packaging, heating materials, and aerospace applications.

[0003] Traditional processes suffer from difficulties in carbon fiber dispersion, low retention of conductive fillers, brittleness and poor toughness of phenolic resin-impregnated carbon fiber paper, and the impact of polytetrafluoroethylene (PTFE) in the microporous layer on conductivity, all of which severely affect the performance of carbon fiber paper. Replacing the traditional alcohol-soluble process with water-soluble phenolic resin allows for the development of a more environmentally friendly method for preparing carbon fiber paper, optimizing product performance and reducing pollution. Simultaneously, improvements to the dispersant and binder systems can significantly enhance the conductivity and mechanical properties of carbon fiber paper. Currently, in the hydrogen energy field, most carbon paper research focuses on its application in gas diffusion layers for fuel cells, with limited research on carbon paper used in proton exchange membrane electrolyzer cathode gas diffusion layers. As a core material for the gas diffusion layer in water electrolysis for hydrogen production, the performance of carbon paper directly determines hydrogen production efficiency and equipment lifespan. In the future, with the explosive growth of the green hydrogen energy industry, carbon paper technology will accelerate its iteration towards high performance, low cost, and environmental friendliness, becoming a key link in promoting the hydrogen economy. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings and deficiencies of the prior art and provide a carbon fiber paper for the gas diffusion layer of an electrolytic cell.

[0005] Another object of the present invention is to provide a method for preparing the carbon fiber paper for the gas diffusion layer of the electrolytic cell described above.

[0006] Another object of the present invention is to provide the application of carbon fiber paper for the gas diffusion layer of the electrolytic cell.

[0007] The objective of this invention is achieved through the following technical solution:

[0008] A method for preparing carbon fiber paper for a gas diffusion layer in an electrolytic cell includes the following steps:

[0009] (1) The carbon fiber was soaked in sodium hydroxide solution, dried and impurities were removed to obtain clean carbon fiber. It was then mixed evenly with amidothiourea and sulfur powder and heated in a tube furnace under an argon atmosphere. After cooling, modified sulfonated carbon fiber was obtained.

[0010] (2) The multi-walled carbon nanotubes were placed in water and ultrasonically treated to obtain a dispersion. 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide were added to the dispersion and stirred for 120 min under ice-water bath conditions. Then ethylenediamine was added and stirred for another 60 min. After vacuum drying, multi-walled carbon nanotubes with amino groups on the surface were obtained.

[0011] (3) Take the modified sulfonated carbon fiber prepared in step (1) and place it in water. Add polyethylene oxide and polyvinylpyrrolidone. After dissolution, a uniformly dispersed carbon fiber solution is obtained.

[0012] (4) Take polyacrylonitrile pulp and multi-walled carbon nanotubes with amino groups on the surface prepared in step (2), add them to the carbon fiber solution prepared in step (3), and obtain a stable dispersed pulp after dispersing for 10 min.

[0013] (5) The pulp prepared in (4) is quickly transferred into the cylinder of the paper machine, and after being filtered to obtain a wet paper web, it is vacuum dried to obtain a carbon paper precursor.

[0014] (6) Dissolve polybenzimidazole in N,N-dimethylacetamide to obtain solution A, and dissolve polyvinyl methyl acetal in acetone to obtain solution B. Mix solution A and solution B, and then add cashew bisphenol A. Stir at 60°C for 60 min to obtain modified polyvinyl methyl acetal solution.

[0015] (7) Transfer the modified polyvinyl alcohol acetal solution prepared in (6) into a flat-bottomed disc, and then put the carbon paper precursor prepared in (5) into it. After soaking for 5 minutes, take it out and drain the excess soaking liquid. Then, vacuum dry the carbon paper precursor to obtain the impregnated carbon paper precursor.

[0016] (8) The impregnated carbon paper precursor prepared in (7) is placed in a flat hot press for hot pressing, cooled and then transferred to a tube furnace for heating under an argon atmosphere to prepare carbon fiber base paper.

[0017] (9) Dissolve zirconium tetrachloride in anhydrous ethanol, then add tetrapropyl titanate, stir for 60 min to prepare sample A, put sample A into a vacuum drying oven to dry, centrifuge at 5000 rpm for 20 min, wash, and prepare sample B. Add tetradecyltrimethylammonium bromide to water, heat in a 50℃ water bath for 60 min, put sample B into it and stir to obtain sample B solution. Add carbon black to water and ultrasonically disperse to obtain carbon black dispersion. Then, add carbon black dispersion to sample B solution, ultrasonically treat to obtain sample C solution, centrifuge at 4000 rpm for 20 min, wash, and prepare hydrophobic conductive coating.

[0018] (10) Apply the hydrophobic and conductive coating to the surface of the carbon fiber base paper prepared in step (8), dry it, and prepare carbon fiber paper that can be used as the gas diffusion layer of the proton exchange membrane electrolyzer.

[0019] The mass ratio of the clean carbon fiber, amidothiourea and sulfur powder in step (1) is 5-8:4-8:0.4-1.

[0020] The heating conditions described in step (1) are to raise the temperature to 1000℃ at a rate of 5℃ / min and hold it for 60min.

[0021] The mass ratio of the multi-walled carbon nanotubes, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide and ethylenediamine in step (2) is 0.3:12:6:12.

[0022] The multi-walled carbon nanotubes described in step (2) have a diameter of 8–15 nm and a length of 30–50 μm.

[0023] The mass ratio of the modified sulfonated carbon fiber, polyethylene oxide and polyvinylpyrrolidone in step (3) is 1-2:0.3:0.2.

[0024] The mass ratio of polyacrylonitrile pulp and amino-coated multi-walled carbon nanotubes in step (4) is 2-4:1-2.

[0025] The mass ratio of polybenzimidazole and N,N-dimethylacetamide in step (6) is 1:10.

[0026] The mass ratio of polyvinyl acetal and acetone in step (6) is 1:10.

[0027] The mass ratio of solution A to solution B in step (6) is 40:60.

[0028] The hot pressing conditions described in step (8) are 160℃ and 15MPa for 20 minutes.

[0029] The heating conditions described in step (8) are to raise the temperature to 1200℃ at a rate of 5℃ / min and hold for 60min.

[0030] The ratio of zirconium tetrachloride to tetrapropyl titanate in step (9) is 0.4:20 mL.

[0031] The mass ratio of tetradecyltrimethylammonium bromide, sample B and carbon black in step (9) is 0.5:1:3.

[0032] The amount of hydrophobic conductive coating applied in step (10) is 2-10 g / m. 2 .

[0033] The drying conditions described in step (10) are drying at 100°C for 20 minutes.

[0034] A method for preparing carbon fiber paper for the gas diffusion layer of an electrolytic cell, wherein the paper is prepared by the above-described preparation method.

[0035] The application of carbon fiber paper for the gas diffusion layer of the electrolyzer in hydrogen production by water electrolysis.

[0036] The present invention has the following advantages and effects compared with the prior art:

[0037] (1) A method for preparing carbon fiber paper for gas diffusion layer in electrolytic cell is provided, wherein carbon fiber is modified by sulfonation and sulfonic acid groups (-SO3H) are introduced on its surface to enhance its hydrophilicity and dispersibility. At the same time, the appropriate use of dispersant can help the carbon fiber to be more uniformly and stably dispersed in aqueous solution.

[0038] (2) Amino groups (-NH2) are used to modify multi-walled carbon nanotubes by amine compounds, giving them amino groups on their surface. These amino groups then interact with the -SO3H groups of the modified carbon fibers, effectively enhancing the bonding force between the two. In addition, polyacrylonitrile pulp with a large specific surface area can improve the retention rate of carbon nanotubes, thereby improving the electrical conductivity, flexural strength, and tensile strength of carbon fiber paper.

[0039] (3) Polyvinyl methyl aldehyde (PVM) was modified using polybenzimidazole. Polybenzimidazole is an aromatic heterocyclic polymer with repeating benzimidazole units in its molecular structure. This unique chemical structure endows it with excellent thermal stability, superior mechanical properties, and excellent chemical inertness, which can effectively improve the problems of insufficient thermal stability and high brittleness of PMM. The addition of cashew nut biphenol successfully introduced flexible long branches, which increased the toughness of PMM and helped to improve the mechanical properties of carbon fiber paper.

[0040] (4) The coating prepared using zirconium tetrachloride, tetrapropyl titanate, tetradecyltrimethylammonium bromide, and carbon black exhibits excellent hydrophobicity, conductivity, and adhesion, effectively solving the problems of high resistance and poor bonding strength inherent in traditional polytetrafluoroethylene emulsions. The carbon fiber paper prepared using this method is simple to operate and can be used in the diffusion layer of proton exchange membrane water electrolysis to produce hydrogen gas, while also enabling industrial production. Attached Figure Description

[0041] Figure 1 The results show the sheet resistance of the carbon paper prepared in the examples and comparative examples.

[0042] Figure 2 These are the tensile strength test results of the carbon paper prepared in the examples and comparative examples.

[0043] Figure 3 These are the bending strength test results of the carbon paper prepared in the examples and comparative examples.

[0044] Figure 4 These are the air permeability test results of the carbon paper prepared in the examples and comparative examples.

[0045] Figure 5 These are the compression rate test results of the carbon paper prepared in the examples and comparative examples.

[0046] Figure 6 These are photographs of the carbon paper precursor and the carbon paper product prepared in Example 1; where A is the carbon paper precursor and B is the carbon paper product. Detailed Implementation

[0047] The present invention will be further described in detail below with reference to the embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto.

[0048] Unless otherwise specified in the following implementation plan, the test conditions are generally as per standard test conditions or the test conditions recommended by the reagent company. Unless otherwise specified, all materials and reagents used are commercially available.

[0049] Raw material source:

[0050] Carbon fiber: Purchased from Hangzhou Gaoke Composite Materials Co., Ltd., length 3mm;

[0051] Polyacrylonitrile pulp: purchased from Changzhou Yaobang Friction Materials Factory, length 1-2mm;

[0052] Multi-walled carbon nanotubes: purchased from Beijing Forsman Technology Co., Ltd., product number 0601006, purity 95%, diameter 8-15nm, length 30-50μm;

[0053] Polybenzimidazole: Purchased from Dongguan Yufeng Plastic & Chemical Co., Ltd.;

[0054] Polyvinyl alcohol acetal: purchased from Shandong Guohua Chemical Co., Ltd.;

[0055] Cashew nut bicarbonate: purchased from Jining Ribuluo Biotechnology Co., Ltd.;

[0056] Carbon black: purchased from Tianjin Yiborui Chemical Co., Ltd., resistivity ≤0.4Ω•m;

[0057] Other chemical reagents: purchased from Shanghai McLean Technology Co., Ltd.

[0058] Example 1

[0059] A method for preparing carbon fiber paper for a gas diffusion layer in an electrolytic cell includes the following steps:

[0060] (1) 10g of carbon fiber was immersed in 2L of sodium hydroxide solution (1.5mol / L) for 40min, and dried at 80℃ to remove surface impurities. 5g of clean carbon fiber, 5g of amidine thiourea and 1g of sulfur powder were taken after treatment, mixed evenly and placed in a tube furnace. The mixture was kept at 1000℃ for 60min under an argon atmosphere with a heating rate of 5℃ / min to obtain modified sulfonated carbon fiber.

[0061] (2) 0.3 g of multi-walled carbon nanotubes were placed in 500 mL of deionized water and sonicated for 40 min to obtain a uniform dispersion. 12 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 6 g of N-hydroxysuccinimide were added to the dispersion and stirred at 600 rpm for 120 min under ice-water bath (0 °C). Then 12 g of ethylenediamine was added and stirred at 500 rpm for 60 min. Finally, the mixture was vacuum dried at 80 °C for 60 min to obtain multi-walled carbon nanotubes with amino groups on the surface.

[0062] (3) Take 1.1304g of the modified sulfonated carbon fiber prepared in step (1) and place it in 1L of deionized water. Add 0.3g of polyethylene oxide and 0.2g of polyvinylpyrrolidone to it and dissolve for 10min to obtain a uniformly dispersed carbon fiber solution.

[0063] (4) Take 0.471g of 60°SR polyacrylonitrile pulp and 0.2826g of multi-walled carbon nanotubes with amino groups on the surface prepared in step (2) and add them to the carbon fiber solution prepared in step (3). After dispersing for 10 minutes, a stable dispersed pulp is obtained.

[0064] (5) The pulp prepared in (4) is quickly transferred into the cylinder of the paper machine. After filtration, a wet paper web is obtained. The paper web is then vacuum dried at 100°C for 10 min to obtain a carbon paper precursor.

[0065] (6) Dissolve 10g of polybenzimidazole in 100g of N,N-dimethylacetamide to obtain solution A, and dissolve 20g of polyvinyl methyl acetal in 200g of acetone to obtain solution B. Mix the solutions according to the mass ratio of solution A: solution B = 40:60. Take 100g of the mixed solution and add 1g of cashew nut biphenol to it. Stir at 600rpm for 60min at 60℃ to obtain modified polyvinyl methyl acetal solution.

[0066] (7) Take 100g of the modified polyvinyl alcohol acetal solution prepared in (6) and transfer it into a flat-bottomed disc. Then, put the carbon paper precursor prepared in (5) into it and soak it for 5 minutes. After soaking, take it out and drain the excess soaking liquid. Put it into a vacuum drying oven at 60°C for 20 minutes to obtain the impregnated carbon paper precursor.

[0067] (8) The impregnated carbon paper precursor prepared in (7) is placed in a flat hot press and hot-pressed at 160°C and 15MPa for 20 min. After cooling, it is transferred to a tube furnace and kept at 1200°C for 60 min in an argon atmosphere to prepare carbon fiber base paper.

[0068] (9) Dissolve 0.4 g of zirconium tetrachloride in 50 mL of anhydrous ethanol, then add 20 mL of tetrapropyl titanate, stir for 60 min to prepare sample A; put sample A into a vacuum drying oven, dry at 200 °C for 20 h, centrifuge at 5000 rpm for 20 min, and wash with deionized water 5 times to prepare sample B; take 0.5 g of tetradecyltrimethylammonium bromide in 50 mL of deionized water, heat in a water bath at 50 °C for 60 min, then add 1 g of sample B and stir to obtain sample B solution; take 3 g of carbon black in 100 mL of deionized water, and ultrasonically disperse for 40 min to obtain carbon black dispersion; then add it to sample B solution, and ultrasonically treat for 30 min to obtain sample C solution; finally, centrifuge at 4000 rpm for 20 min, and wash with deionized water 5 times to prepare hydrophobic conductive coating.

[0069] (10) Take 0.314g of hydrophobic conductive coating and coat it on the surface of the carbon fiber base paper prepared in (8). Dry it at 100℃ for 20min to prepare carbon fiber paper that can be used for the gas diffusion layer of proton exchange membrane electrolyzer.

[0070] Example 2

[0071] A method for preparing carbon fiber paper for a gas diffusion layer in an electrolytic cell includes the following steps:

[0072] (1) 10g of carbon fiber was immersed in 2L sodium hydroxide solution (2mol / L) for 40min, and dried at 80℃ to remove surface impurities. 8g of clean carbon fiber, 4g of amidine thiourea and 0.4g of sulfur powder were taken after treatment, mixed evenly and placed in a tube furnace. The mixture was kept at 1000℃ for 60min under an argon atmosphere with a heating rate of 5℃ / min to obtain modified sulfonated carbon fiber.

[0073] (2) 0.3 g of multi-walled carbon nanotubes were placed in 500 mL of deionized water and sonicated for 40 min to obtain a uniform dispersion. 12 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 6 g of N-hydroxysuccinimide were added to the dispersion and stirred at 600 rpm for 120 min under ice-water bath (0 °C). Then 12 g of ethylenediamine was added and stirred at 500 rpm for 60 min. Finally, the mixture was vacuum dried at 80 °C for 60 min to obtain multi-walled carbon nanotubes with amino groups on the surface.

[0074] (3) Take 1.3188g of the modified sulfonated carbon fiber prepared in step (1) and place it in 1L of deionized water. Add 0.2g of polyethylene oxide and 0.2g of polyvinylpyrrolidone to it and dissolve for 10min to obtain a uniformly dispersed carbon fiber solution.

[0075] (4) Take 0.3768g of 50°SR polyacrylonitrile pulp and 0.1884g of multi-walled carbon nanotubes with amino groups on the surface prepared in step (2) and add them to the carbon fiber solution prepared in step (3). After dispersing for 10 minutes, a stable dispersed pulp is obtained.

[0076] (5) The pulp prepared in (4) is quickly transferred into the cylinder of the paper machine. After filtration, a wet paper web is obtained. The paper web is then vacuum dried at 100°C for 10 min to obtain a carbon paper precursor.

[0077] (6) Dissolve 10g of polybenzimidazole in 100g of N,N-dimethylacetamide to obtain solution A. At the same time, dissolve 20g of polyvinyl methyl acetal in 200g of acetone to obtain solution B. Mix the solutions A and B at a mass ratio of 50:50. Then add 2g of cashew nut biphenol and stir at 600rpm for 60min at 60℃ to obtain a modified polyvinyl methyl acetal solution.

[0078] (7) Take 100g of the modified polyvinyl alcohol acetal solution prepared in (6) and transfer it into a flat-bottomed disc. Then, put the carbon paper precursor prepared in (5) into it and soak it for 5 minutes. After soaking, take it out and drain the excess soaking liquid. Put it into a vacuum drying oven at 60°C for 20 minutes to obtain the impregnated carbon paper precursor.

[0079] (8) The impregnated carbon paper precursor prepared in (7) is placed in a flat hot press and hot-pressed at 180°C and 10MPa for 20 min. After cooling, it is transferred to a tube furnace and kept at 1200°C for 60 min in an argon atmosphere to prepare carbon fiber base paper.

[0080] (9) Dissolve 0.4 g of zirconium tetrachloride in 50 mL of anhydrous ethanol, then add 20 mL of tetrapropyl titanate, stir for 60 min to prepare sample A; put sample A into a vacuum drying oven, dry at 200 °C for 20 h, centrifuge at 5000 rpm for 20 min, and wash with deionized water 5 times to prepare sample B; take 0.5 g of tetradecyltrimethylammonium bromide in 50 mL of deionized water, heat in a water bath at 50 °C for 60 min, then add 1 g of sample B and stir to obtain sample B solution; take 3 g of carbon black in 100 mL of deionized water, and ultrasonically disperse for 40 min to obtain carbon black dispersion; then add it to sample B solution, and ultrasonically treat for 30 min to obtain sample C solution; finally, centrifuge at 4000 rpm for 20 min, and wash with deionized water 5 times to prepare hydrophobic conductive coating.

[0081] (10) Take 0.2512g of hydrophobic conductive coating and coat it on the surface of the carbon fiber base paper prepared in (8). Dry it at 100℃ for 20min to prepare carbon fiber paper that can be used for the gas diffusion layer of proton exchange membrane electrolyzer.

[0082] Example 3

[0083] A method for preparing carbon fiber paper for a gas diffusion layer in an electrolytic cell includes the following steps:

[0084] (1) 10g of carbon fiber was immersed in 2L of sodium hydroxide solution (1.5mol / L) for 40min, and dried at 80℃ to remove surface impurities. 5g of clean carbon fiber, 5g of amidine thiourea and 1g of sulfur powder were taken after treatment, mixed evenly and placed in a tube furnace. The mixture was kept at 1000℃ for 60min under an argon atmosphere to obtain modified sulfonated carbon fiber.

[0085] (2) 0.3 g of multi-walled carbon nanotubes were placed in 500 mL of deionized water and sonicated for 40 min to obtain a uniform dispersion. 12 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 6 g of N-hydroxysuccinimide were added to the dispersion and stirred at 600 rpm for 120 min under ice-water bath (0 °C). Then 12 g of ethylenediamine was added and stirred at 500 rpm for 60 min. Finally, the mixture was vacuum dried at 80 °C for 60 min to obtain multi-walled carbon nanotubes with amino groups on the surface.

[0086] (3) Take 1.5072g of the modified sulfonated carbon fiber prepared in step (1) and place it in 1L of deionized water. Add 0.3g of polyethylene oxide and 0.2g of polyvinylpyrrolidone to it and dissolve for 10min to obtain a uniformly dispersed carbon fiber solution.

[0087] (4) Take 0.2826g of 70°SR polyacrylonitrile pulp and 0.0942g of multi-walled carbon nanotubes with amino groups on the surface prepared in step (2) and add them to the carbon fiber solution prepared in step (3). After dispersing for 10 minutes, a stable dispersed pulp is obtained.

[0088] (5) The pulp prepared in (4) is quickly transferred into the cylinder of the paper machine. After filtration, a wet paper web is obtained. The paper web is then vacuum dried at 100°C for 10 min to obtain a carbon paper precursor.

[0089] (6) Dissolve 10g of polybenzimidazole in 100g of N,N-dimethylacetamide to obtain solution A. At the same time, dissolve 20g of polyvinyl methyl acetal in 200g of acetone to obtain solution B. Mix the solutions A and B at a mass ratio of 40:60. Then add 1g of cashew nut biphenol. Stir at 600rpm for 60min at 60℃ to obtain a modified polyvinyl methyl acetal solution.

[0090] (7) Take 100g of the modified polyvinyl alcohol acetal solution prepared in (6) and transfer it into a flat-bottomed disc. Then, put the carbon paper precursor prepared in (5) into it and soak it for 5 minutes. After soaking, take it out and drain the excess soaking liquid. Put it into a vacuum drying oven at 60°C for 20 minutes to obtain the impregnated carbon paper precursor.

[0091] (8) The impregnated carbon paper precursor prepared in (7) is placed in a flat hot press and hot-pressed at 160°C and 15MPa for 20 min. After cooling, it is transferred to a tube furnace and kept at 1200°C for 60 min in an argon atmosphere to prepare carbon fiber base paper.

[0092] (9) Dissolve 0.4 g of zirconium tetrachloride in 50 mL of anhydrous ethanol, then add 20 mL of tetrapropyl titanate, stir for 60 min to prepare sample A; put sample A into a vacuum drying oven, dry at 200 °C for 20 h, centrifuge at 5000 rpm for 20 min, and wash with deionized water 5 times to prepare sample B; take 0.5 g of tetradecyltrimethylammonium bromide in 50 mL of deionized water, heat in a water bath at 50 °C for 60 min, then add 1 g of sample B and stir to obtain sample B solution; take 3 g of carbon black in 100 mL of deionized water, and ultrasonically disperse for 40 min to obtain carbon black dispersion; then add it to sample B solution, and ultrasonically treat for 30 min to obtain sample C solution; finally, centrifuge at 4000 rpm for 20 min, and wash with deionized water 5 times to prepare hydrophobic conductive coating.

[0093] (10) Take 0.314g of hydrophobic conductive coating and coat it on the surface of the carbon fiber base paper prepared in (8). Dry it at 100℃ for 20min to prepare carbon fiber paper that can be used for the gas diffusion layer of proton exchange membrane electrolyzer.

[0094] Example 4

[0095] A method for preparing carbon fiber paper for a gas diffusion layer in an electrolytic cell includes the following steps:

[0096] (1) 10g of carbon fiber was immersed in 2L of sodium hydroxide solution (1.5 mol / L) for 40min, and dried at 80℃ to remove surface impurities. 5g of carbon fiber, 5g of amidine thiourea and 1g of sulfur powder were taken after treatment, mixed evenly and placed in a tube furnace. The mixture was kept at 1000℃ for 60min under an argon atmosphere to obtain modified sulfonated carbon fiber.

[0097] (2) 0.3 g of multi-walled carbon nanotubes were placed in 500 mL of deionized water and sonicated for 40 min to obtain a uniform dispersion. 12 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 6 g of N-hydroxysuccinimide were added to the dispersion and stirred at 600 rpm for 120 min under ice-water bath (0 °C). Then 12 g of ethylenediamine was added and stirred at 500 rpm for 60 min. Finally, the mixture was vacuum dried at 80 °C for 60 min to obtain multi-walled carbon nanotubes with amino groups on the surface.

[0098] (3) Take 1.6956g of the modified sulfonated carbon fiber prepared in step (1) and place it in 1L of deionized water. Add 0.4g of polyethylene oxide and 0.4g of polyvinylpyrrolidone to it and dissolve for 10min to obtain a uniformly dispersed carbon fiber solution.

[0099] (4) Take 0.0942g of 60°SR polyacrylonitrile pulp and 0.0942g of multi-walled carbon nanotubes with amino groups on the surface prepared in step (2) and add them to the carbon fiber solution prepared in step (3). After dispersing for 10 minutes, a stable dispersed pulp is obtained.

[0100] (5) The pulp prepared in (4) is quickly transferred into the cylinder of the paper machine. After filtration, a wet paper web is obtained. The paper web is then vacuum dried at 100°C for 10 min to obtain a carbon paper precursor.

[0101] (6) Dissolve 10g of polybenzimidazole in 100g of N,N-dimethylacetamide to obtain solution A. At the same time, dissolve 20g of polyvinyl methyl acetal in 200g of acetone to obtain solution B. Mix the solutions A and B at a mass ratio of 40:60. Then add 1g of cashew nut biphenol. Stir at 600rpm for 60min at 60℃ to obtain a modified polyvinyl methyl acetal solution.

[0102] (7) Take 100g of the modified polyvinyl alcohol acetal solution prepared in (6) and transfer it into a flat-bottomed disc. Then, put the carbon paper precursor prepared in (5) into it and soak it for 5 minutes. After soaking, take it out and drain the excess soaking liquid. Put it into a vacuum drying oven at 60°C for 20 minutes to obtain the impregnated carbon paper precursor.

[0103] (8) The impregnated carbon paper precursor prepared in (7) is placed in a flat hot press and hot-pressed at 160°C and 15MPa for 20 min. After cooling, it is transferred to a tube furnace and kept at 1200°C for 60 min in an argon atmosphere to prepare carbon fiber base paper.

[0104] (9) Dissolve 0.4 g of zirconium tetrachloride in 50 mL of anhydrous ethanol, then add 20 mL of tetrapropyl titanate, stir for 60 min to prepare sample A; put sample A into a vacuum drying oven, dry at 200 °C for 20 h, centrifuge at 5000 rpm for 20 min, and wash with deionized water 5 times to prepare sample B; take 0.5 g of tetradecyltrimethylammonium bromide in 50 mL of deionized water, heat in a water bath at 50 °C for 60 min, then add 1 g of sample B and stir to obtain sample B solution; take 3 g of carbon black in 100 mL of deionized water, and ultrasonically disperse for 40 min to obtain carbon black dispersion; then add it to sample B solution, and ultrasonically treat for 30 min to obtain sample C solution; finally, centrifuge at 4000 rpm for 20 min, and wash with deionized water 5 times to prepare hydrophobic conductive coating.

[0105] (10) Take 0.314g of hydrophobic conductive coating and coat it on the surface of the carbon fiber base paper prepared in (8). Dry it at 100℃ for 20min to prepare carbon fiber paper that can be used for the gas diffusion layer of proton exchange membrane electrolyzer.

[0106] Comparative Example 1

[0107] Following the steps of Example 1, but replacing the sulfonation modification of carbon fiber in step (1) with plasma oxidation treatment of carbon fiber, the specific steps are as follows: 10g of carbon fiber is immersed in 2L of sodium hydroxide solution (1.5mol / L) for 40min, and then dried at 80℃ to remove surface impurities. The clean carbon fiber is then plasma oxidized for 20min under conditions of 200W power, 40sccm gas flow rate and 100Pa vacuum to obtain modified carbon fiber. Other operations are consistent with Example 1 to obtain carbon fiber paper for the gas diffusion layer of the electrolytic cell.

[0108] Comparative Example 2

[0109] Referring to the steps of Example 1, the difference is that the method of amylation modification of carbon nanotubes in step (2) is replaced by guanidine modification of carbon nanotubes using nitric acid and guanidine derivatives to prepare guanidine-modified carbon nanotubes. The specific operation steps are as follows:

[0110] 0.3 g of multi-walled carbon nanotubes were placed in 500 mL of 70% nitric acid and treated at 80 °C for 120 min. After washing and drying, the nanotubes were placed in a beaker, and an appropriate amount of deionized water and 1,1,3,3-tetramethylguanidine were added. The mixture was reacted at 90 °C for 240 min. After washing and drying, guanidine-modified carbon nanotubes were obtained.

[0111] Other operations are consistent with those in Example 1, and carbon fiber paper for the gas diffusion layer of the electrolytic cell is obtained.

[0112] Comparative Example 3

[0113] The preparation was carried out according to the method of Example 1, except that the polyvinyl acetal in step (6) was replaced with an equal amount of thermoplastic phenolic resin to prepare a modified phenolic resin solution. The remaining steps were the same as in Example 1 to obtain carbon fiber paper for the gas diffusion layer of the electrolytic cell.

[0114] Comparative Example 4

[0115] The preparation was carried out according to the method of Example 1, except that the polybenzimidazole in step (6) was replaced with an equal amount of benzoxazine to prepare a modified polyvinyl alcohol methyl acetal resin solution. The remaining steps were the same as in Example 1 to obtain carbon fiber paper for the gas diffusion layer of the electrolytic cell.

[0116] Comparative Example 5

[0117] The preparation was carried out according to the method of Example 1, except that the cashew nut biphenol in step (6) was replaced with an equal amount of cashew nut phenol to prepare a modified polyvinyl alcohol methyl acetal resin solution. The remaining steps were the same as in Example 1 to obtain carbon fiber paper for the gas diffusion layer of the electrolytic cell.

[0118] Comparative Example 6

[0119] The preparation was carried out according to the method of Example 1, except that zirconium tetrachloride in step (9) was replaced with an equal amount of zirconium oxychloride to prepare sample A. The remaining steps were the same as in Example 1 to obtain carbon fiber paper for the gas diffusion layer of the electrolytic cell.

[0120] Comparative Example 7

[0121] The preparation was carried out according to the method of Example 1, except that the tetrapropyl titanate in step (9) was replaced with an equal amount of tetrabutyl titanate to prepare sample A. The remaining steps were the same as in Example 1 to obtain carbon fiber paper for the gas diffusion layer of the electrolytic cell.

[0122] Comparative Example 8

[0123] The preparation was carried out according to the method of Example 1, except that the tetradecyltrimethylammonium bromide in step (9) was replaced with an equal amount of hexadecyltrimethylammonium bromide to prepare sample B solution. The remaining steps were the same as in Example 1 to obtain carbon fiber paper for the gas diffusion layer of the electrolytic cell.

[0124] Comparative Example 9

[0125] The preparation was carried out according to the method of Example 1, except that the carbon black dispersion in step (9) was replaced with an equal amount of graphene dispersion to prepare sample C solution. The remaining steps were the same as in Example 1 to obtain carbon fiber paper for the gas diffusion layer of the electrolytic cell.

[0126] Comparative Example 10

[0127] The preparation was carried out according to the method of Example 1, except that the hydrophobic conductive coating in step (10) was replaced with an equal amount of polytetrafluoroethylene emulsion, and the remaining steps were the same as in Example 1, to obtain carbon fiber paper for the gas diffusion layer of the electrolytic cell.

[0128] Example 5 Performance testing and characterization of carbon paper

[0129] 5.1 Performance Testing Methods

[0130] The carbon fiber paper obtained in the examples and comparative examples was subjected to performance testing. The testing methods included:

[0131] (1) Resistivity test: The resistivity of carbon fiber paper was measured using a low resistance tester;

[0132] (2) Tensile strength test: The tensile strength of carbon fiber paper was tested using a universal testing machine;

[0133] (3) Bending strength test: The bending strength of carbon fiber paper was tested using a three-point bending test device;

[0134] (4) Air permeability test: The air permeability of carbon fiber paper was tested using an air permeability meter;

[0135] (5) Compression ratio test: The tensile strength of carbon fiber paper is tested using a universal testing machine.

[0136] 5.2 Performance Test Results and Comparison

[0137] The results are as follows Figures 1-5 As shown, it can be seen that:

[0138] The difference between Comparative Example 1 and Example 1 is that: plasma oxidation treatment was used to treat carbon fibers; since the binding force between the -COOH group introduced on the surface of carbon fibers and the -NH2 group on the surface of carbon nanotubes by the plasma oxidation method is not as strong as the binding force between the -COOH group and the -SO3H sulfonic acid group, the binding force between carbon fibers and aminated carbon nanotubes in aqueous solution becomes worse, which leads to a decrease in the conductivity, mechanical properties and air permeability of carbon paper.

[0139] The difference between Comparative Example 2 and Example 1 is that carbon nanotubes are modified by guanidine using nitric acid and guanidine derivatives. Since the binding force between the -NH-C(=NH)-NH2 group introduced on the surface of carbon nanotubes by the guanidine modification method and the -SO3H group on the surface of carbon fiber is not as strong as the binding force between the -NH2 group and the -SO3H sulfonic acid group, the binding force between sulfonated carbon fiber and carbon nanotubes becomes worse in aqueous solution, resulting in a decrease in the conductivity, mechanical properties and air permeability of carbon paper.

[0140] The difference between Comparative Example 3 and Example 1 is that: polybenzimidazole was used to modify an equal mass of phenolic resin; since the modification and strengthening effect of polybenzimidazole on phenolic resin is not as good as that of polyvinyl acetal, the overall performance of the impregnation solution is reduced, and the strengthening effect on the carbon paper during the impregnation process is small, resulting in a downward trend in the conductivity, mechanical properties and air permeability of the carbon paper.

[0141] The difference between Comparative Example 4 and Example 1 is that: benzoxazine was used to modify polyvinyl methyl aldehyde. Since the heat resistance, mechanical properties and toughness of benzoxazine are not as good as those of polybenzimidazole, the strengthening modification effect on polyvinyl methyl aldehyde is weak, and the strengthening effect on carbon paper during impregnation is small, resulting in a decrease in the conductivity, mechanical properties and air permeability of the carbon paper.

[0142] The difference between Comparative Example 5 and Example 1 is that: cashew nut shell powder was used to modify polyvinyl methyl aldehyde. Since cashew nut shell powder is less reactive and tough than cashew nut shell powder, its strengthening effect on polyvinyl methyl aldehyde is weaker, and its strengthening effect on carbon paper is smaller during impregnation. As a result, the conductivity, mechanical properties and air permeability of the carbon paper show a downward trend.

[0143] The difference between Comparative Example 6 and Example 1 is that Sample A was prepared using the same mass of zirconium oxychloride. Since the reactivity of zirconium oxychloride and tetrapropyl titanate is not as good as that of zirconium tetrachloride, the overall performance of Sample A is poor, which affects the subsequent coating preparation process, resulting in a decrease in the conductivity, mechanical properties and air permeability of the carbon paper.

[0144] The difference between Comparative Example 7 and Example 1 is that Sample A was prepared using an equal mass of n-butyl titanate. Since the reactivity of zirconium tetrachloride and n-butyl titanate is not as good as that of n-propyl titanate, the overall performance of Sample A is poor, which affects the subsequent coating preparation process, resulting in a decrease in the conductivity, mechanical properties and air permeability of the carbon paper.

[0145] The difference between Comparative Example 8 and Example 1 is that Sample C was prepared using equal mass of hexadecyltrimethylammonium bromide; since the reactivity of Sample B and hexadecyltrimethylammonium bromide is not as good as that of tetradecyltrimethylammonium bromide, the overall performance of Sample B solution is poor, which affects the subsequent coating preparation process, resulting in a decrease in the conductivity, mechanical properties and air permeability of the carbon paper.

[0146] The difference between Comparative Example 9 and Example 1 is that graphene of equal mass was used to replace carbon black in the preparation of carbon paper. Since graphene is less dispersible in water than carbon black, it affects the uniformity of the coating, resulting in a decrease in the conductivity, mechanical properties and air permeability of the carbon paper.

[0147] The difference between Comparative Example 10 and Example 1 is that carbon paper is coated with an equal mass of polytetrafluoroethylene emulsion. Since polytetrafluoroethylene emulsion itself has certain insulating properties, but its mechanical properties are not as good as the coating prepared in this patent, the microporous layer it forms has a certain impact on the performance of carbon paper, resulting in a decrease in the conductivity, mechanical properties and air permeability of the carbon paper.

[0148] In summary, the carbon fiber paper for the gas diffusion layer of the electrolyzer of the present invention employs amidothiourea and sulfur powder to sulfonate carbon fibers. Simultaneously, amine compounds are used to aminate and modify multi-walled carbon nanotubes. Therefore, carbon fibers with -SO3H groups on their surface can form a good bond with carbon nanotubes with -NH2 groups on their surface, enhancing the mechanical and electrical properties of the carbon paper. Furthermore, the addition of polyacrylonitrile pulp with a large specific surface area also improves the retention rate of carbon nanotubes. During the impregnation process, the mechanical properties and toughness of polyvinyl methyl acetal modified with polybenzimidazole and cashew nut shell glycoside are significantly enhanced, effectively improving the tensile and flexural strength of the carbon fiber paper. Finally, the self-made hydrophobic and conductive coating further enhances the overall performance of the carbon fiber paper. Therefore, the carbon fiber paper prepared using this method can be applied to the gas diffusion layer of proton exchange membrane water electrolysis for hydrogen production.

[0149] The main performance indicators of carbon paper used in the gas diffusion layer of proton exchange membrane water electrolysis for hydrogen production are: resistivity, as the gas diffusion layer must provide a conduction channel for electrons between the bipolar plate and the catalyst layer and collect current; mechanical properties, including tensile strength, flexural strength, and compressibility, to ensure the carbon paper maintains its strength in the presence of large amounts of water; and gas permeability to ensure the effective transport of the generated gas. Therefore, the carbon fiber paper prepared in this invention can be used in the gas diffusion layer of proton exchange membrane water electrolysis for hydrogen production.

[0150] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for preparing carbon fiber paper for a gas diffusion layer in an electrolytic cell, characterized in that... Includes the following steps: (1) The carbon fiber was soaked in sodium hydroxide solution, dried and impurities were removed to obtain clean carbon fiber. It was then mixed evenly with amidothiourea and sulfur powder and heated in a tube furnace under an argon atmosphere. After cooling, modified sulfonated carbon fiber was obtained. (2) The multi-walled carbon nanotubes were placed in water and ultrasonically treated to obtain a dispersion. 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and N-hydroxysuccinimide were added to the dispersion and stirred for 120 min under ice-water bath conditions. Then ethylenediamine was added and stirred for another 60 min. After vacuum drying, multi-walled carbon nanotubes with amino groups on the surface were obtained. (3) Take the modified sulfonated carbon fiber prepared in step (1) and place it in water. Add polyethylene oxide and polyvinylpyrrolidone. After dissolution, a uniformly dispersed carbon fiber solution is obtained. (4) Take polyacrylonitrile pulp and multi-walled carbon nanotubes with amino groups on the surface prepared in step (2), add them to the carbon fiber solution prepared in step (3), and obtain a stable dispersed pulp after dispersing for 10 min. (5) The pulp prepared in (4) is quickly transferred into the cylinder of the paper machine, filtered to obtain a wet paper web, and vacuum dried to obtain a carbon paper precursor. (6) Dissolve polybenzimidazole in N,N-dimethylacetamide to obtain solution A, and dissolve polyvinyl methyl acetal in acetone to obtain solution B. Mix solution A and solution B, and then add cashew bisphenol A. Stir at 60°C for 60 min to obtain modified polyvinyl methyl acetal solution. (7) Transfer the modified polyvinyl alcohol acetal solution prepared in (6) into a flat-bottomed disc, and then put the carbon paper precursor prepared in (5) into it. After soaking for 5 minutes, take it out and drain the excess soaking liquid. Then, vacuum dry the carbon paper precursor to obtain the impregnated carbon paper precursor. (8) The impregnated carbon paper precursor prepared in (7) is placed in a flat hot press for hot pressing, cooled and then transferred to a tube furnace for heating under an argon atmosphere to prepare carbon fiber base paper. (9) Dissolve zirconium tetrachloride in anhydrous ethanol, then add tetrapropyl titanate, stir for 60 min to prepare sample A, put sample A into a vacuum drying oven to dry, centrifuge at 5000 rpm for 20 min, wash, and prepare sample B. Add tetradecyltrimethylammonium bromide to water, heat in a 50℃ water bath for 60 min, put sample B into it and stir to obtain sample B solution. Add carbon black to water and ultrasonically disperse to obtain carbon black dispersion. Then, add carbon black dispersion to sample B solution, ultrasonically treat to obtain sample C solution, centrifuge at 4000 rpm for 20 min, wash, and prepare hydrophobic conductive coating. (10) Apply the hydrophobic and conductive coating to the surface of the carbon fiber base paper prepared in step (8), dry it, and prepare carbon fiber paper that can be used as the gas diffusion layer of the proton exchange membrane electrolyzer.

2. The method for preparing carbon fiber paper for the gas diffusion layer of an electrolytic cell according to claim 1, characterized in that: The mass ratio of the clean carbon fiber, amidothiourea, and sulfur powder in step (1) is 5-8:4-8:0.4-1; The heating conditions described in step (1) are to raise the temperature to 1000℃ at a rate of 5℃ / min and hold it for 60min.

3. The method for preparing carbon fiber paper for the gas diffusion layer of an electrolytic cell according to claim 1, characterized in that: The mass ratio of the multi-walled carbon nanotubes, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, N-hydroxysuccinimide and ethylenediamine in step (2) is 0.3:12:6:12; The multi-walled carbon nanotubes described in step (2) have a diameter of 8–15 nm and a length of 30–50 μm.

4. The method for preparing carbon fiber paper for the gas diffusion layer of an electrolytic cell according to claim 1, characterized in that: The mass ratio of the modified sulfonated carbon fiber, polyethylene oxide and polyvinylpyrrolidone in step (3) is 1-2:0.3:0.

2.

5. The method for preparing carbon fiber paper for the gas diffusion layer of an electrolytic cell according to claim 1, characterized in that: The mass ratio of polyacrylonitrile pulp and amino-coated multi-walled carbon nanotubes in step (4) is 2-4:1-2.

6. The method for preparing carbon fiber paper for the gas diffusion layer of an electrolytic cell according to claim 1, characterized in that: The mass ratio of polybenzimidazole and N,N-dimethylacetamide in step (6) is 1:10; The mass ratio of polyvinyl acetal and acetone in step (6) is 1:10; The mass ratio of solution A to solution B in step (6) is 40:

60.

7. The method for preparing carbon fiber paper for the gas diffusion layer of an electrolytic cell according to claim 1, characterized in that: The hot pressing conditions described in step (8) are 160℃ and 15MPa for 20 minutes; The heating conditions described in step (8) are to raise the temperature to 1200℃ at a rate of 5℃ / min and hold for 60min.

8. The method for preparing carbon fiber paper for the gas diffusion layer of an electrolytic cell according to claim 1, characterized in that: The ratio of zirconium tetrachloride to tetrapropyl titanate in step (9) is 0.4:20 mL; The mass ratio of tetradecyltrimethylammonium bromide, sample B, and carbon black in step (9) is 0.5:1:3; The amount of hydrophobic conductive coating applied in step (10) is 2-10 g / m. 2 ; The drying conditions described in step (10) are drying at 100°C for 20 minutes.

9. A method for preparing carbon fiber paper for a gas diffusion layer in an electrolytic cell, wherein the paper is prepared by any one of the preparation methods described in claims 1 to 8.

10. The application of the carbon fiber paper for the gas diffusion layer of the electrolyzer as described in claim 9 in the electrolysis of water to produce hydrogen.